Health Insurance Benefit Mandates and the Firm-Size Distribution - James Bailey; Douglas A. Webber (Institute for the Study of Labor (IZA), 2015)
By 2010, the average US state had passed 37 health insurance benefit mandates (laws requiring health insurance plans to cover certain additional services). Previous work has shown that these mandates likely increase health insurance premiums, which in turn could make it more costly for firms to compensate employees. Using 19962010 data from the Quarterly Census of Employment and Wages and a novel instrumental variables strategy, we show that there is limited evidence that mandates reduce employment. However, we find that mandates lead to a distortion in firm size, benefiting larger firms that are able to self-insure and thus exempt themselves from these state-level health insurance regulations. This distortion in firm size away from small businesses may lead to substantial decreases in productivity and economic growth.
Keywords: L51; I13; I18; J32; 330; health insurance; benefit mandates; self-insurance; interest groups; employment; firm size